The Influence of Character Values of Bing Bunny Toward the Young Learner Character Value Education in TK Aisyiyah - Abdilah, Bagus; Wahyuni, Sri; Fadilaturrahmah, Fadilaturrahmah (Jurnal Locus Penelitian dan Pengabdian, 2025)
Character values in education refer to ethical principles that influence an individual's actions, including values like honesty, responsibility, respect, and tolerance. This study aims to determine the influence of the Bing Bunny animation on character education for early childhood at TK Aisyiyah. Character education at an early age is essential for forming a strong foundation of good personality traits in children, such as honesty, responsibility, and politeness. This research uses a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation. The subjects of this study are teachers and students at TK Aisyiyah. The findings show that the Bing Bunny animation positively influences the instillation of character values in children. Through simple stories and engaging visuals, children can more easily understand and imitate the good behaviors demonstrated by the main character. This study concludes that animated media like Bing Bunny can serve as an effective tool to support character education in early childhood education institutions.